Analysis of the ecological parameters of the diesel engine powered with biodiesel fuel containing methyl esters from Camelina sativa Oil - Sergejus Lebedevas; Galina Lebedeva; Violeta Makarevičienė; Irina Kazanceva; Kiril Kazancev (Transport, 2010)
The article explores the possibilities of using fatty acid methyl esters derived from the oil of a new species of oily plant Camelina sativa not demanding on soil. The performed research on the physical and chemical properties of pure methyl esters from Camelina sativa show that biofuels do not meet requirements for the biodiesel fuel standard (LST EN 14214:2009) of a high iodine value and high content of linoleic acid methyl ester, so they must be mixed with methyl esters produced from pork lard the content of which in the mixture must be not less than 32%. This article presents the results of tests on combustion emission obtained when three‐cylinder diesel engine VALMET 320 DMG was fuelled with a mixture containing 30% of this new kind of fuel with fossil diesel fuel comparing with emissions obtained when the engine was fuelled with a fuel mixture containing 30% of conventional biodiesel fuel (rapeseed oil methyl esters) with fossil diesel fuel. The obtained results show that using both types of fuel, no significant differences in CO and NOx concentrations were observed throughout the tested load range. When operating on fuels containing methyl esters from Camelina sativa, HC emissions decreased by 10 to 12% and the smokeness of exhaust gas by 12 to 25%.